2004
DOI: 10.1111/j.1432-2277.2004.tb00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IGL-1, a new preservation solution, on kidney grafts (a pre-clinical study)

Abstract: Ischemia-reperfusion injury conditions short-term and longterm graft function. The effects of the inversion of K + and N a + concentrations and substitution with polyethylene glycol for hydroxyethyl starch in University of Wisconsin (K-UW) solution were evaluated in isolated perfused rat kidneys and in autotransplanted pig kidneys. In the rat model kidneys were cold-stored for 24 h in K-UW or Na-UW or Na-PEG UW solutions (IGL-I solution). Fractional sodium reabsorption and glomerular filtration rate was better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…The presence of 1 g/L of PEG35000 stabilized the DPPC monolayer in the gaseous phase more strongly than PEG20000. This could be in agreement with the higher effectiveness of PEG35000 against cold-induced injuries observed in our cellular preservation model and also with the higher protection of PEG35000 observed during organ transplantation [3,4,11].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The presence of 1 g/L of PEG35000 stabilized the DPPC monolayer in the gaseous phase more strongly than PEG20000. This could be in agreement with the higher effectiveness of PEG35000 against cold-induced injuries observed in our cellular preservation model and also with the higher protection of PEG35000 observed during organ transplantation [3,4,11].…”
Section: Discussionsupporting
confidence: 79%
“…The inclusion of hydroxyethyl starch (HES) in the so-called University of Wisconsin (UW) solution, the standard preservation solution used in transplantation, has become increasingly controversial, and it has been suggested that HES could be efficiently replaced by polyethylene glycols (PEGs) [1,2]. Recent reports have shown that substituting HES by a 35,000 Da PEG (PEG35000) in an extracellular UW-like solution (IGL-1®) improved rat liver viability or pig kidney function [3,4]. In addition, our group has previously demonstrated in an auto-transplanted pig kidney model the beneficial effect on early and long-term cold ischemia-reperfusion injury of a saline solution with a composition mimicking an extracellular milieu and containing a 20,000 Da PEG (PEG20000) [5].…”
mentioning
confidence: 99%
“…Other studies which have found that some PEG (8000 and 20 000 Da) improved other organs preservation suggested that PEG may be a valuable additive to a possible multiple organ liquid (28,29). In addition, recent reports showed that substituting PEG35 (1 g/L) for hydroxyethyl starch in an extracellular UW-like solution (IGL-1) improved rat liver viability or pig kidney function (20,30). Unexpectedly, we found that IGL-1 was inadequate for 24 h cell preservation whereas PEG 35 000 Da Protection in Kidney Cell Preservation adding only as little as 1 g/L of PEG35 in a very simple extracellular-type solution preserved more than 80% against cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PEG induces a significant reduction of MHC class II expression on the cell surfaces, which plays an important role in ischemia/reperfusion injury as it enhances graft immunogenicity. There is a clear correlation between the degree of overexpression of MHC class II and CD4+ infiltrating cells, peritubular expression of VCAM‐1 and development of interstitial fibrosis (5, 6, 8).…”
mentioning
confidence: 99%